Interdisciplinary Collaboration for LGBTQ Students in Foster Care: Strategies for School Counselors. Issue Volume 12:Issues 4(2018) (2nd October 2018) - Beck, Matthew J.; Maier, Candice A.; Means, Alicia; Isaacson, Lauren A.
Abstract: Unsafe and ill-prepared school environments exist for many lesbian, gay, bisexual, transgender, and queer (LGBTQ) students in foster care. School counselors are uniquely positioned to develop safe and inclusive schools for this vulnerable student population; however, strategies for interdisciplinary collaboration and advocacy with schools, families, and systems incorporated with LGBTQ youth in foster care are limited. This article explores how school counselors can advocate across disciplines for LGBTQ youth in foster care, including K-12 education systems, family/caregivers, and social service organizations providers.